The cost of treating mucormycosis with isavuconazole compared with standard therapy in the UK. (May 2017) - Bagshaw, Emma; Kuessner, Daniel; Posthumus, Jan; Escrig, Cesar; Blackney, Michael; Heimann, Sebastian Marcel; Cornely, Oliver Andreas
Aim: Mucormycosis is a fungal infection associated with high mortality. Until recently, the only licensed treatments were amphotericin B (AMB) formulations. Isavuconazole (ISAV) is a new mucormycosis treatment. A UK-based economic model explored treatment costs with ISAV versus liposomal AMB followed by posaconazole.Materials & methods: As a matched case–control analysis showed similar efficacy for ISAV and AMB, a cost-minimization approach was taken. Direct costs – drug acquisition, monitoring and administration, and hospitalization costs – were estimated from the National Health Service perspective.Results: Per-patient costs for ISAV and liposomal AMB + posaconazole were UK£26, 810 and UK£41, 855, respectively, with savings primarily driven by drug acquisition and hospitalization costs.Conclusion: ISAV may reduce costs compared with standard mucormycosis therapy.